Communication apprehension in the online presentational speaking course: Considerations for synchronous course meetings and asynchronous presentations. Issue 1 (2nd January 2023) - Ledford, Victoria; Wang, Xiaojing; Anderson, Lindsey B.; Leach, Jonathan; Lucas, Melissa; Mazzone, Raphael
ABSTRACT: As institutions of higher education continue to offer online instruction, educators and administrators of presentational speaking courses must adapt their classes for various modes of online delivery. One primary consideration for adapting a presentational speaking course to online delivery is how students will experience communication apprehension and/or public speaking anxiety in online communication contexts. The instructional communication field is rife with research about students' experiences with speech anxiety and communication apprehension. However, little work has explored how students' experiences may differ when the primary mode of course communication and course presentations is mediated through either synchronous or asynchronous modes of online communication. If these anxieties in face-to-face settings can deter students' academic and professional goals (Richmond et al., Communication apprehension, avoidance, and effectiveness [6th ed., Pearson, 2013]), researchers should investigate students' experiences in online courses. The current study begins to fill this gap. We analyze qualitative responses ( N  = 178) to an open-ended survey distributed to undergraduates in presentational speaking courses. Thematic analysis revealed the uniqueness of online communication apprehension and its similarities to face-to-face communication apprehension. Implications for administrators and instructors of presentational speaking courses are offered.